Maximizing Post-exercise Anabolism: The Case for Relative Protein Intakes - Moore, Daniel R. (Frontiers in Nutrition, 2019)
Maximizing the post-exercise increase in muscle protein synthesis, especially of the contractile myofibrillar protein fraction, is essential to facilitate effective muscle remodelling and enhance hypertrophic gains with resistance training. MPS is the primary regulated variable influencing muscle net balance with dietary amino acid ingestion representing the single most important nutritional variable enhancing post-exercise rates of muscle protein synthesis. Dose-response studies in average (i.e. ~80kg) males have reported an absolute 20g dose of high quality, rapidly digested protein maximizes mixed and myofibrillar protein synthetic rates. However, it is unclear if these absolute protein intakes can be viewed in a ‘one size fits all’ solution. Re-analysis of published literature suggests a relative single meal intake of ~0.31g/kg of rapidly digested, high quality protein (i.e. whey) should be considered as a nutritional guideline for individuals of average body composition aiming to maximize post-exercise myofibrillar protein synthesis while minimizing irreversible amino acid oxidative catabolism that occurs with excessive intakes of this macronutrient. This muscle-specific bolus intake is lower than that reported to maximize whole body anabolism (i.e. ≥0.5g/kg). Review of the available literature suggests that potential confounders such as the co-ingestion of carbohydrate, sex, and amount of active muscle mass do not represent significant barriers to the translation of this objectively determined relative protein intake. Additional research is warranted to elucidate the effective dose for proteins with suboptimal amino acid compositions (e.g. plant-based) and/or slower digestion rates as well as whether recommendations are appreciably affected by other physiological conditions such high habitual daily protein ingestion, aging, obesity, and/or periods of chronic negative energy balance.